Distorse Information Technology to Endanger Depression in Diabetes Mellitus Patients - Erwin Purwaningsih; Zulkifli Umar; Nurhasanah (Poltanesa, 2025)
More than half of the mental health problems that impact one-third of individuals with diabetes mellitus go undiagnosed. Stress has an effect on physical health in addition to upsetting the mind. Distorse is e-learning about respondents' mental health and e-health in the form of mobile health (which includes apps, technology, and health resources).The early diagnosis approach for depressed conditions experienced by individuals with diabetes mellitus undergoing treatment has been modernized with the Sobat Antasari method. The purpose of this study is to keep people with diabetes mellitus mentally healthy and lower their depression levels. The 66 respondents in this quasi-experimental study were split into two (two) groups using proportional random sampling, and the study included a pretest-posttest design with a control group. The depression anxiety stress scales (DASS), an internationally validated questionnaire, are the instrument utilized in this study. With a p-value of 0.036, the study's findings demonstrated that the Early Detection of Fatality Caused by Diabetes Mellitus intervention group was impacted by efforts to employ Distorse media. This demonstrates that the degree of depression before and after the use of book media and Distorse applications differs significantly. However, with a p-value of 0.299>0.05, the control group, which received simply mental health book media, did not show any significant evaluation outcomes. The combination intervention of book media and Distorse applications has been shown to be effective in significantly lowering the level of depression in patients with diabetes mellitus.